Early weaning in beef cattle production - Cattelam, Jonatas (Revista de Ciências Agroveterinárias, 2014)
With the aim of improving the reproductive rates of breeding herds, the weaning of calves at younger ages, between 60 to 90 days is done. However some farmers don’t do this handling commitment due to the animal’s future performance. It is recognized that calves weaned earlier show underperformance compared to those that stay with the cow for the conventional weaning period. Thus, feeding strategies that minimize the performance drop must be sought in order for calves show appropriate pregnancy rates as well as slaughter and carcass weight that don’t harm the sales of these animals. Thus, the present study aims to conduct a review of the impact of early weaning on beef cattle production.